Perioperative anticoagulation in free microvascular flaps – a comparison of different prophylactic regimes in oncologic reconstructive surgery - Tamse, Henriette; Koch, Michael; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Sievert, Matti (European Review for Medical and Pharmacological Sciences, 2024)
OBJECTIVE: Free tissue transfer has an established place in oncologic head and neck surgery. However, the necessity and specific regimen of perioperative thromboprophylaxis remain controversial. Here, the risk of postoperative hemorrhage contrasts with vascular pedicle thrombosis and graft loss. This work compares three different heparin protocols (AC) with regard to postoperative complications. PATIENTS AND METHODS: A retrospective analysis of our free flap transplants between 2004 and 2023 was conducted. Inclusion criteria were thromboprophylaxis with (A) 500 IU/h unfractionated heparin (UFH), (B) low-molecular-weight heparin (LMWH) once daily, and (C) LMWH once daily with additional immediate preoperative administration. Primary endpoints were the incidence of postoperative bleeding and hematoma and the appearance of flap thrombosis. RESULTS: We evaluated 355 cases, 87 in group A, 179 in group B, and in group C 89 patients. Overall, postoperative bleeding occurred in 8.7% of patients, and 83% underwent hemostasis under intubation anesthesia, with no significant difference between groups (p = 0.784). Hematoma formation requiring revision was found in 3.7% of patients (p = 0.660). We identified postoperative hematoma as a significant influencing factor for venous pedicle thrombosis (OR 3.602; p = 0.001). Venous and arterial flap thrombosis in the graft vessel showed no difference between the groups (p = 0.745 and p = 0.128). CONCLUSIONS: The three anticoagulation regimens appear to be equivalent therapy for the prevention of thrombosis without significant differences in postoperative bleeding. The use of LMWH with additional preoperative administration can, therefore, be administered in free flap reconstruction.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Anticoagulation; Bleeding; Flap thrombosis; Free flap; Hematoma; Heparin; Microvascular reconstruction